2020
DOI: 10.1371/journal.pone.0233766
|View full text |Cite
|
Sign up to set email alerts
|

Inter-professional teamwork and its association with patient safety in German hospitals—A cross sectional study

Abstract: BackgroundInter-professional teamwork is a prominent factor in quality of care and may lead to improved patient safety. Although team members' points of view are highly relevant when trying to improve inpatient procedures, there is a lack of systematic assessment of their perceptions. Therefore, study aims were to explore inter-professional teamwork, safety-related behavior, and patient safety in German hospitals from team members' point of view. Furthermore, we wanted to examine the association between inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
2
18
0
5
Order By: Relevance
“…Such a finding has already been reported in several other studies (e.g. Dinius et al., 2020 ; O’Leary et al., 2010 ). A factor contributing to this phenomenon could be the traditionally pronounced hierarchies within medicine (compare O’Leary et al., 2012 ), which can become problematic when nurses do not find a suitable opportunity or do not dare to address problematic aspects.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Such a finding has already been reported in several other studies (e.g. Dinius et al., 2020 ; O’Leary et al., 2010 ). A factor contributing to this phenomenon could be the traditionally pronounced hierarchies within medicine (compare O’Leary et al., 2012 ), which can become problematic when nurses do not find a suitable opportunity or do not dare to address problematic aspects.…”
Section: Discussionsupporting
confidence: 83%
“…From a previous study dealing with expectations, communication and collaboration in nursing homes (Meyer-Kühling et al, 2015), it is known that nursing staff assessed the collaboration more negatively and felt less valued compared to physicians. Another study conducted in hospitals also reports that nurses assess these aspects more negatively than physicians (Dinius et al, 2020). This is alarming because a good and respectful relationship between physicians and nurses can contribute to higher job satisfaction and higher job retention for nurses (Galletta et al, 2013) which, in turn, leads to better patient care (Koy et al, 2015).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…There are 34% respondents that have a work length 6-10 years (Tables 1 and 2). Our results resonate with other studies that had reported work experience affect work ability [27], where the period of employment is significantly associated with good working relationships and knowledge integration problems [28]. A multicenter longitudinal study in 13 hospitals in Germany found that work experience and period of employment was associated with interprofessional collaboration perception (good working relationship), particularly between 1 and 3 months versus 1-5 years, but not more than 5 years.…”
Section: Work Length Influences Relationships Among Memberssupporting
confidence: 91%
“…Moreover, perceptions of inter-professional teamwork within wards seemed similar across professional groups due to the impact of ward affiliation. This study suggests training entire interprofessional teams in future interventions [28].…”
Section: Work Length Influences Relationships Among Membersmentioning
confidence: 84%
“…Constatou-se na maioria das pesquisas encontradas, que a colaboração e a comunicação aprimorada no trabalho das EID's e EMD's de AVC podem funcionar como um facilitador para a tomada de decisões em intervenções para pacientes (Johnson et al, 2015;Singh et al, 2015;Munce et al, 2017;Abhijit et al, 2019;Obana et al, 2019). Esses resultados estão de acordo com estudos recentes que indicam que a comunicação e colaboração eficazes da equipe interdisciplinar envolvendo pacientes com AVC, familiares, médicos, enfermeiras, fisioterapeutas, terapeutas ocupacionais, fonoaudiólogos, psicólogos, assistentes sociais e outros, são essenciais para maximizar os resultados da reabilitação em que o trabalho em equipe é um processo central e os resultados clínicos obtidos pelos pacientes, são essenciais para avaliar a qualidade dos cuidados pósagudos (Dinius et al, 2020).…”
Section: Discussionunclassified